D' Layla Fruitcake / Sya' Azli Abd Aziz - Abd Aziz, Sya' Azli (2018)
D'Layla Fruitcake Facebook page is an online business that created in 29 October 2018 for the purpose of academic study. It is an assignment that been tasked to students for subject Principles of Entrepreneurship (ENT530) in UiTM. In this assignment students are required to create a business via social media platform (Facebook). Whereas in this assignment shall develop student ability to demonstrate information retrieval and management skill related to a business via social media platform. This online business is dedicated to provide customers the very best of our product, with a focus on cakes or fruitcake to be significant. We shall try our best to give best experience to the customer or buyer delicious fruitcakes that baked with various kinds of fruits. In addition to the novel ordering process, customers are assured a moist and flavoursome fruitcake, made fresh daily with the best locally sourced and natural ingredients.